Multi‐sectoral interventions for healthy growth. Issue 3 (18th September 2013) - del Carmen Casanovas, Ma; Lutter, Chessa K.; Mangasaryan, Nune; Mwadime, Robert; Hajeebhoy, Nemat; Aguilar, Ana Maria; Kopp, Ciro; Rico, Luis; Ibiett, Gonzalo; Andia, Doris; Onyango, Adelheid W.
Abstract: The risk of stunted growth and development is affected by the context in which a child is born and grows. This includes such interdependent influences as the political economy, health and health care, education, society and culture, agriculture and food systems, water and sanitation, and the environment. Here, we briefly review how factors linked with the key sectors can contribute to healthy growth and reduced childhood stunting. Emphasis is placed on the role of agriculture/food security, especially family farming; education, particularly of girls and women; water, sanitation, and hygiene and their integration in stunting reduction strategies; social protection including cash transfers, bearing in mind that success in this regard is linked to reducing the gap between rich and poor; economic investment in stunting reduction including the work with the for‐profit commercial sector balancing risks linked to marketing foods that can displace affordable and more sustainable alternatives; health with emphasis on implementing comprehensive and effective health care interventions and building the capacity of health care providers. We complete the review with examples of national and subnational multi‐sectoral interventions that illustrate how critical it is for sectors to work together to reduce stunting.